Update on the epidemiology, risk factors and disease outcomes of Juvenile idiopathic arthritis. Issue 2 (April 2018) - Palman, Jason; Shoop-Worrall, Stephanie; Hyrich, Kimme; McDonagh, Janet E.
Abstract: Juvenile idiopathic arthritis (JIA) is the most common inflammatory joint condition of childhood and represents seven JIA subtypes characterised by distinct clinical and laboratory variables. Genetic and environmental factors are known to influence JIA, although many unanswered questions remain. Measurement of health outcomes in JIA is imperative for both clinical practice and research. Patient-reported outcomes present particular challenges in paediatric rheumatology in view of the importance of collecting reports from both the child/young person and the parent. Another challenge is the need for continuity of outcome measurement across the paediatric–adult interface during the process of transition in terms of both measurement tools and the mechanisms in the system to facilitate tracking of the young person into adult care. Finally, the need for adults with JIA to be seen as a distinct group in adult rheumatology practice is important for both service provision and outcome research.